Poverty and child health in the UK: using evidence for action. Issue 8 (8th February 2016) - Wickham, Sophie; Anwar, Elspeth; Barr, Ben; Law, Catherine; Taylor-Robinson, David
Abstract : There are currently high levels of child poverty in the UK, and for the first time in almost two decades child poverty has started to rise in absolute terms. Child poverty is associated with a wide range of health-damaging impacts, negative educational outcomes and adverse long-term social and psychological outcomes. The poor health associated with child poverty limits children's potential and development, leading to poor health and life chances in adulthood. This article outlines some key definitions with regard to child poverty, reviews the links between child poverty and a range of health, developmental, behavioural and social outcomes for children, describes gaps in the evidence base and provides an overview of current policies relevant to child poverty in the UK. Finally, the article outlines how child health professionals can take action by (1) supporting policies to reduce child poverty, (2) providing services that reduce the health consequences of child poverty and (3) measuring and understanding the problem and assessing the impact of action.